WORKLOAD ANALYSIS SEBAGAI METODE UNTUK MENGETAHUI BEBAN KERJA SERTA OPTIMALISASI KERJA KARYAWAN PADA PERUSAHAAN CDE - Rahmawati Syam; Farhan Farhan; Sitti Meyditha Zhafirah Firna; Muh Pajrul Syawal; Syamsul Bakhri Gaffar; Siti Rahmayani Mangnguluang (Jurnal Kebajikan: Pengabdian Kepada Masyarakat, 2023)
The purpose of this workload analysis activity is to carry out human resource management in increasing the productivity of a company. This activity was carried out for 30 employees in technical and production positions using interview and observation techniques which were carried out in two sessions. The process of carrying out workload analysis is to collect job profiles from each position to serve as a reference during the interview process, analyze job profiles to find out job descriptions from the subject to be interviewed, arrange the workload analysis implementation schedule, conduct interviews, process, and input the interview results and make a final summary of the workload analysis results for presentation material in power point. The results of the workload analysis implementation are different workload categories for each position such as normal workloads, high workloads (overloads) and low workloads (underloads), the number of workers needed to complete a work process and knowing the efficiency work processes in a work unit. The benefits felt by the company after conducting workload analysis for employees are knowing the amount of labor needed to complete a job so that there is no shortage of manpower planning (MPP).